(untitled) (Diversity Research: Journal of Analysis and Trends, 2025)
This article explores the historical evolution of tourism from ancient civilizations to the modern globalized world. It examines socio-economic, technological, and cultural factors that shaped tourism practices in the past and contrasts them with contemporary trends influenced by digitalization, sustainability, and global mobility. The study evaluates how tourism has transformed in purpose, scale, accessibility, and cultural impact. Furthermore, the article analyzes current challenges facing the tourism industry, including environmental sustainability, crisis resilience, and technological disruption. The findings highlight the dynamic nature of tourism as both an economic activity and a cultural phenomenon